1975
DOI: 10.1007/bf00585986
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine response of the rat kidney after saline loading, sodium restriction and hemorrhagia

Abstract: Experiments were performed on three groups of rats. The first group consisted of sodium loaded (SL) rats (high sodium diet, 10 meq Na/day, the second group consisted of sodium restricted (SR) rats (low sodium diet, 0.7 meq Na/day) and the third group consisted of hemorrhagic rats (HR), which were bled with 1-1,5% of the body weight. Blood pressure, glomerular filtration rate (GFR) and sodium excretion were measured. In some animals renal blood flow (RBF) was recorded with an electromagnetic flow meter. Adenosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 13 publications
2
43
0
Order By: Relevance
“…Under such circumstances, a further increase in adenosine levels by exogenous administration would not have any additional effect on afferent arterioles with macula densa attached. These observations are compatible with previous reports that adenosine decreases renin release in sodium-depleted animals (Tagawa and Vander 1970;Osswald et al 1975Osswald et al , 1978 but not in sodium-loaded animals (Osswald et al 1975(Osswald et al , 1978. Since endogenous adenosine levels are high in sodium-loaded animals, exogenous adenosine does not inhibit renin release further.…”
Section: (Spielman and Thompson 1982)supporting
confidence: 92%
See 1 more Smart Citation
“…Under such circumstances, a further increase in adenosine levels by exogenous administration would not have any additional effect on afferent arterioles with macula densa attached. These observations are compatible with previous reports that adenosine decreases renin release in sodium-depleted animals (Tagawa and Vander 1970;Osswald et al 1975Osswald et al , 1978 but not in sodium-loaded animals (Osswald et al 1975(Osswald et al , 1978. Since endogenous adenosine levels are high in sodium-loaded animals, exogenous adenosine does not inhibit renin release further.…”
Section: (Spielman and Thompson 1982)supporting
confidence: 92%
“…Osswald et al (1980) have shown that infusion of hypertonic saline into the thoracic aorta elevates renal tissue adenosine and decreases ATP, whereas increasing the sodium load to the kidney decreases renin release through a tubular mechanism involving the macula densa. In addition, intrarenal infusion of adenosine has been shown to decrease renin release in sodium-depleted animals (Tagawa and Vander 1970;Osswald et al 1975Osswald et al , 1978. Thus intrarenal formation of adenosine may play an important role in the control of renin release …”
Section: Role Of Adenosine In Macula Densa Control Of Renin Releasementioning
confidence: 99%
“…From the results of experiments in the dog and rat it has been concluded that adenosine might play a role in the regulation of renal blood flow and glomerular filtration rate (Ono, Inagaki & Hashimoto, 1966;Tagawa & Vander, 1970;Haddy & Scott, 1971;Ueda, 1972;Osswald, Schmitz & Heidenreich, 1975). In addition to its direct vascular effects, adenosine potentiates the vasoconstrictor effect of noradrenaline (NA) (Hashimoto, 1971; and sympathetic nerve stimulation .…”
Section: Introductionmentioning
confidence: 99%
“…Substantial experimental evidence supports the existence of a synergistic interaction between adenosine and the renin-angiotensin system in regulating renal hemodynamics (Hall et al, 1985;Hall and Granger, 1986;Wang et al, 1992;Munger and Jackson, 1994;Navar et al, 1996;Traynor et al, 1998). Early studies showed that suppression of the renin-angiotensin system by feeding a high-sodium diet (Osswald et al, 1975) or administration of an angiotensin-converting enzyme inhibitor (Hall et al, 1985) blunts the renal vasoconstrictor action of adenosine. Micropuncture studies (Munger and Jackson, 1994) have shown that angiotensin II type 1 receptor blockade with losartan markedly attenuates afferent arteriolar vasodilation induced by a selective adenosine A 1 receptor antagonist, 1,3-dipropyl-8-cyclopentylxanthine.…”
mentioning
confidence: 99%